2022
DOI: 10.1155/2022/8080308
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Pharmacists toward Biosimilar Medicines: A Survey in Jordan

Abstract: Aims. Pharmacists in all clinical settings are recognized drug experts and integral educators of biosimilar medicines. Therefore, the objective of this study was to assess pharmacists’ knowledge, predictors of knowledge, and views toward biosimilar medicines in Jordan. Methods. A cross-sectional study was conducted in Jordan during October–December 2020. An Internet-based self-administrated questionnaire on knowledge and views was distributed using social media groups to the pharmacists among different areas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…A reluctance to prescribe biosimilars among clinicians in the Middle East has been observed as a result of a limited understanding of biosimilars and a lack of confidence in its efficacy and safety [ 13 , 20 ]. Furthermore, some surveys found that pharmacists lacked adequate information about biosimilars in order to advise patients appropriately [ 38 , 39 ]. Moreover, negative perceptions towards biosimilars can occur among patients because of the misconception that the lower cost of biosimilars is associated with inferior quality and poorer outcomes compared with reference products [ 40 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
“…A reluctance to prescribe biosimilars among clinicians in the Middle East has been observed as a result of a limited understanding of biosimilars and a lack of confidence in its efficacy and safety [ 13 , 20 ]. Furthermore, some surveys found that pharmacists lacked adequate information about biosimilars in order to advise patients appropriately [ 38 , 39 ]. Moreover, negative perceptions towards biosimilars can occur among patients because of the misconception that the lower cost of biosimilars is associated with inferior quality and poorer outcomes compared with reference products [ 40 ].…”
Section: Overarching Principles and Consensus Recommendationsmentioning
confidence: 99%
“…Importantly, pharmacists have biopharmaceutics knowledge ( Oqal et al, 2022 , Shawahna et al, 2022 ) which supposed to qualify their role in enhancing medication treatment outcomes and promoting wellness, through ensuring dispensing and preparing medications in the correct doses and frequency, and counseling patients for safe and appropriate use of medications ( Mansur 2016 ). In fact, health care professionals rely on and trust pharmacists in selecting and administering medications that promote the quality of life for patients, based on their specialized expertise in medication ( Shawahna et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%